Effect of the Molecular Architecture on the Internal Complexation Behavior of Linear Copolymers and Miktoarm Star Polymers. Issue 2 (2nd January 2015) - Hebbeker, Pascal; Plamper, Felix A.; Schneider, Stefanie
Abstract : Star polymers with arms of two different homopolymers with a weak mutual attraction have been investigated using a coarse grained polymer model and Monte Carlo (MC) simulations. The effect of the polymer architecture on the complexation behavior has been studied for various numbers of arms (up to 8) starting from a diblock copolymer and compared to diblock copolymers as well as alternating linear copolymers. It was found that the star architecture promotes an internal complexation, which is indicated by a reduction of the end‐to‐end distance of the polymer chains. The local concentration of the weakly attractive partners is important to promote their interaction and to harvest the attraction. The results were compared to experimental data. Abstract : Polymeric systems consisting of two different weakly attractive components are investigated using Monte Carlo simulations, comparing various architectures. When arranged in a miktoarm star polymer, complexation is promoted compared to a linear block copolymer and a strictly alternating copolymer.